(untitled) (Research, Society and Development, 2021)
The genus Weissella is composed of bacteria classified as Gram-positive, catalase negative, non-spore forming, coccoid morphology or short bacilli. They belong to the group of lactic acid bacteria (LAB), mainly by production of lactic acid from the fermentation of carbohydrates. Weissella species are distributed in different habitats, such as soils, milking machines, sugar cane and some strains with interesting technological features can be isolated from fermented foods, such as cheeses made from raw milk, fermented vegetables and fermented milk. From the point of view of food technology, some strains have potential in the production of exopolysaccharides, non-digestible oligosaccharides, which is beyond their probiotic potential. Therefore, the bacteria belonging to the genus Weissella might have great technological importance, being also involved in the control of foodborne diseases by production of bacteriocins and hydrogen peroxide. This genus has great potential for use in the food industry.